ANALISIS PENGARUH LEVERAGE, UKURAN PERUSAHAAN, DAN PERTUMBUHAN TERHADAP PROFITABILITAS PERUSAHAAN SUB SEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ningrum, Wulan Setia (Gapenas Publisher, 2025)
This study aims to analyze the effect of Leverage (Debt to Equity Ratio), Company Size, and Growth on Profitability (Return on Equity) in property and real estate companies listed on the Indonesia Stock Exchange (IDX) in 2020-2023. This study uses a quantitative approach. The population in this study is all property and real estate companies listed on the IDX for the 2020-2023 period. The data used are secondary data, with sampling techniques using the purposive sampling method so that a total of 18 companies were obtained as samples or 72 samples during 4 years of observation. Data analysis was carried out through Descriptive Statistical Test, Classical Assumption Test, Multiple Linear Regression Test and Hypothesis Test, with the help of SPSS software version 25. The results of the study show that partially, Leverage and Company Growth have a significant negative effect on Profitability, while Company Size shows a significant positive influence on Profitability. Simultaneously, the three independent variables which include Leverage, Company Size, and Company Growth have a significant influence on the company's Profitability